Desenvolvimento de um modelo de biofilme microcosmos para o estudo da candidíase vulvovaginal - Andrade, Ana Raquel Colares de (2018)
Candida species are commensal of the human microbiota. When in dysbiosis, they express several virulence factors, such as biofilms. Biofilms are complex communities resistant to the host immunity and antibiotics. In human mucosa, Candida spp. biofilms are related to a large number of clinical and epidemiological relevance infections, such as vulvovaginal candidiasis (CVV). The present study aimed to establish a microcosm biofilm model (BMi) in vitro for the study of CVV. Overall, eleven vaginal secretion from patients CVV suspected were used for testes. Of 11, six samples were used to preliminary test aiming to determine the ideal chemical composition of the medium, temperature, growth time and atmospheric gases for biofilm formation. The results were evaluated for the number of colony forming units (CFU / mL), metabolic activity and biomass. Then, others five clinical samples were tested in a previously listed as the most favorable to microbial growth for BMi formation condition; the species of Candida spp. were also isolated for monospecies biofilm (BMo) formation. The models were evaluated for the number of CFU / mL, metabolic and proteolytic activity, biomass and susceptibility to fluconazole (FLC). The BMi morphology was also analyzed by scanning electron microscopy and confocal microscopy. The diagnosis based on phenotypic methods, PCR and MALDI-TOF revealed that C. albicans (10/11) and C. glabrata (1/11) were the etiological agents of the CVV cases investigated. In both models (BMi and BMo), clinical samples and isolated cultures were grown in Vaginal Fluid Simulator Medium at 35ºC for 48 to 72 hours in microaerophilic cells. The results showed lower concordance between the values of CFU / mL and metabolic activity in BMi (1/5) than BMo (5/5). The proteolytic activity was constant in both biofilm models in all samples (n = 5). Biomass quantification revealed higher value in BMi than in BMo in all the samples analyzed (n = 5). BMi cultures showed tolerance to FLC up to 128 μg / mL, with reduction of cell viability only at the concentration of 256 μg / mL. In the BMo model the viability was reduced by up to 50% in the concentrations 256 and 512 μg / mL of FLC. The images revealed the predominance of Candida sp. in BMi - even in the samples that had mixed microbiota. The proposed model for the study of sessile communities in microcosms can be useful as a platform for in vitro studies to improve the pathophysiology explanation and understanding of CVV.